Optimalisasi Pemanfaatan Limbah Pertanian Sebagai Pupuk Organik Dan Pakan Budidaya Ikan Untuk Meningkatkan Perekonomian Masyarakat Desa Bulotalangi Barat - Julhim S. Tangio; Weny J.A Musa; Opir Rumape; Rahnan Lamusu; Suchi Wulandari Dai; Nindiyawati H Maku; Meyrin Hamzzah; Sri Deby R.S Dude (Universitas Negeri Gorontalo, 2022)
West Bulotalangi Village is one of the villages in East Bulango District, Bone Bolango Regency. Most of the economic activities of the people of West Bulotalangi are engaged in the agricultural sector. The dominant people's livelihoods are farmers and ranchers. One of the efforts made by the community is catfish farming. However, catfish farmers are experiencing a problem, namely the price of circulating fish feed has increased while the price of catfish is relatively cheap. Therefore, to increase the selling price of catfish, several programs were held from KKN-T Merdeka Learning Campus students, namely making catfish feed so that it makes it easier for the community to cultivate catfish because the materials used are relatively cheap and easy to obtain, there is also processing of catfish into processed products which are one of the solutions to the problem to increase the economic value of catfish. In addition, in the agricultural sector, the program proposed by KKN-T MBKM students was the manufacture of BOKHASI fertilizer (Biological Rich Organic Material) by utilizing agricultural waste and then processing it into fertilizer. For this reason, efforts are needed to be able to increase the knowledge and skills of the people of West Bulotalangi Village related to making fertilizer, making fish feed, and strategies for developing processed products. The method used is the empowerment of the target group including learning techniques in the form of theory and simulation to the target community and also direct practice of the manufacturing process with students and the community.Keywords: Agricultural waste, catfish, fertilizer.